2022
DOI: 10.3390/antiox11020288
|View full text |Cite
|
Sign up to set email alerts
|

Na+/K+-ATPase Alpha 2 Isoform Elicits Rac1-Dependent Oxidative Stress and TLR4-Induced Inflammation in the Hypothalamic Paraventricular Nucleus in High Salt-Induced Hypertension

Abstract: Background: Numerous studies have indicated that a high salt diet inhibits brain Na+/K+-ATPase (NKA) activity, and affects oxidative stress and inflammation in the paraventricular nucleus (PVN). Furthermore, Na+/K+-ATPase alpha 2-isoform (NKA α2) may be a target in the brain, taking part in the development of salt-dependent hypertension. Therefore, we hypothesized that NKA α2 regulates oxidative stress and inflammation in the PVN in the context of salt-induced hypertension. Methods: Part I: We assessed NKA sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Microinjection of yohimbine to block α2R or DETC to increase superoxide levels in the PVN almost abolished the roles of intravenous administration of DEX in inhibiting LPS-induced changes in RSNA, MAP and HR ( Figure 7 D). It is known that oxidative stress and inflammation in the PVN increase sympathetic outflow [ 16 , 46 ]. The present study has shown that NADPH oxidase-derived superoxide production in the PVN mediates the inhibitory effects of DEX on sympathetic activity as we described above.…”
Section: Resultsmentioning
confidence: 99%
“…Microinjection of yohimbine to block α2R or DETC to increase superoxide levels in the PVN almost abolished the roles of intravenous administration of DEX in inhibiting LPS-induced changes in RSNA, MAP and HR ( Figure 7 D). It is known that oxidative stress and inflammation in the PVN increase sympathetic outflow [ 16 , 46 ]. The present study has shown that NADPH oxidase-derived superoxide production in the PVN mediates the inhibitory effects of DEX on sympathetic activity as we described above.…”
Section: Resultsmentioning
confidence: 99%
“…SOD1 is an important antioxidant enzyme which inhibits ROS production [ 32 ]. Some studies have shown that elevated NOX activity and ROS production in the PVN stimulates abnormal peripheral SNA in high-salt or Ang II-induced hypertension rats [ 38 , 41 ]. Blocking the excessive production of ROS in PVN can inhibit SNA in hypertensive rats [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also found that NF-κB activities in the PVN are closely associated with the intensity of SNA in hypertensive rats [ 24 , 47 ]. NF-κB and oxidative stress in PVN play crucial roles in the pathogenesis of hypertension [ 38 , 48 ]. SIRT1 can directly act on NF-κB and reduce the acetylation level of p65 subunit Lys 310 , thereby inhibiting the transcription activity of NF-κB [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 , 94 IL-38 inhibited human adipocyte differentiation and reduced secretion of inflammatory cytokines, IL-1β and MCP-1, 95 and IL-38 reduction of joint inflammation involved the NF-κB signaling pathway also known to be involved in hypertension. 96 , 97 Macrophages, smooth muscle cells and vascular endothelial cells also release IL-38 under apoptotic conditions and affect the circulatory Bcl-2/Bax/Caspase-3 signaling pathway, attenuating hyperlipidemia. 68 , 94 No direct relationship between IL-38 and hypertension has yet been shown but this molecule does seem to ameliorate the disorder ( Figure 2 ).…”
Section: Regulation Of Interleukin-1 Family In Cardiovascular Diseasesmentioning
confidence: 99%